Effect of grid-screen on bubble characteristics of vertically discharged bubble plumes. (18th May 2022) - Behzadipour, Arsalan; Azimi, Amir H.; Lima Neto, Iran E.
Highlights: The effect of grid-screen on the mixing capacity of bubble plumes was tested. The grid-screen can reduce the vertical velocity of bubbles by 38%. Bubble concentration increased by 9% as the distance after grid-screen increased. The effect of grid-screen became negligible at a certain distance after the screen. Bubble size growth after the grid-screen is correlated with Reynolds number. Abstract: A series of laboratory experiments was conducted to improve the entrainment and mixing capacity of vertically discharged bubble plumes by employing a grid-screed with different openings and at different distances from the nozzle. Bubble characteristics such as bubble size, bubble size distribution, bubble concentration, and bubble velocity were measured using an accurate Refractive Bubble Index (RBI) probe along the plume, before, and after the grid-screen. The effects of grid-screen openings and airflow discharge on variations of bubble characteristics were examined. Experimental results showed that the size of grid-screen and its distance from the nozzle decreased the vertical velocity of bubbles by an average of 38%. Dynamics of bubbles before and after the grid-screen was analyzed and a regime classification was proposed based on variations of the normalized bubble velocity with the distance from the nozzle. It was found that increasing the distance between the grid-screen and nozzle increased bubble concentration by approximately 9% and reduced bubble size by 31%. At a certain distance from the nozzle, the effect of the grid-screen became negligible and bubble velocity reached its initial value. This specific distance was extracted for all tests and the results showed that such critical distance was correlated with the nozzle Reynolds number. Empirical correlations were developed to estimate the effective mixing length after the grid-screen. The proposed equations were found to be correlated with the bubble Reynolds number.